A study of the effectiveness of the contextual lab activity in the teaching and learning engineering statistics at the Universiti Tun Hussein Onn Malaysia (UTHM) - Md Amin, Zulkarnain

(untitled)
Inaccurate concept in statistics contributes to the assumption by the students that statistics do not relate to the real world and is not revelent to the engineering field. There are universities who introduced learning statisticsusing statistics lab activities. However the learning is more on the learning how to use software and not to enhance the knowledge in statistics. Thus this reasearch was done to test the effectiveness of the contextual lab activities in learning engineering statistics for the engineering students in UTHM. The objectives of this research is to identify the level of understanding, motivation, and acceptance between the students who had gone through the contextual lab activity and the non contextual lab activity based on the questionnaire. The quiz result was measured using the independent t-test. This research is done using the quasi-experiment. There were 265 civil, mechanical and electric students who were taking BSM 2922 Engineering Statistics for their 2nd semester session 2007/2008. The sample consisted of 155 students which were divided into two groups : 72 engineering degree students in the treated group and 83 engineering degree students in the control group. The treated group followed the contextual lab activity while the control group followed the non contextual lab activity. The findings showed that there is no significant difference between the level of understanding and motivation from both groups. However there is a significant difference for the acceptance level between both groups. The findings also show that there is a significant difference for the Postest mean score between the two groups. The treated group who had gone through the contextual lab activity scored higher than the non contextual . In conclusion, the contextual lab activity is able to help the engineering statistics students in their learning process.